Trójmorze – czyja inicjatywa? - Leszek Kuk (Nowa Polityka Wschodnia, 2021)
The “Three-Seas area” project and the activities of the Three-Seas Initiative, i.e. the deepened cooperation of 12 Central European Member States of the European Union, which appeared in 2015, quickly gained considerable popularity in Poland. It has even been recognized as the flagship project of the Polish right wing grouped around the Law and Justice party, which took power in that same year 2015. In the “Three Seas” was seen another emanation of the idea of the so-called Intermarium, present in Polish political tradition since at least 1918. Meanwhile, the “Three Seas” project was prepared in the autumn of 2014 in the United States by the influential Atlantic Council think tank and included in a comprehensive document entitled “Completing Europe. From the North-South Corridor to Energy, Transportation, and Telecommunications Union Completing Europe”. The implementation of its assumptions would not, however, be limited to the modernization and strengthening of infrastructure connections between the aforementioned 12 states located in the NorthSouth belt from Estonia to Croatia and Bulgaria, which were planned to participate in the project. It would also mean the strengthening of their economic ties with the United States, a far-reaching weakening of their economic ties with Russia, and, most importantly, their “independence” in relation to the strong states of the “former Union” with Germany at the fore. The role of an intermediary in gaining the support of the Central European states was assigned to the new (since February 2015) president of Croatia, Kolinda GrabarKitarović, well known in the decision-making circles of the USA, NATO, and the European Union. It quickly recruited the new Polish president, Andrzej Duda, who represents the largest and most pro-American state of the Three Seas countries. These activities made it possible to establish an “organization” on September 29, 2015, during a meeting in New York, attended by 11/12 “leaders” of Central European states and 3 representatives of the Atlantic Council management. The Three Seas Initiative, defined as the “presidential platform”, is constantly expanding the fields of its activity, but it is still regarded as a relatively weak structure with an uncertain future. The sources of its relative internal weakness include, firstly, large differences in the potentials, political positions, and geopolitical orientations of the individual member states of the Initiative, and secondly - the opposing influence of external factors. The United States’ aspirations to make the Initiative “transatlantic” have been discreetly opposed since 2018 by the actions of the EU and the German authorities directed towards its “Europeanization”, that is, towards the harmonization of its activities with the position of the Union.